Correlations between DW‐MRI and 18F‐FDG PET/CT parameters in head and neck squamous cell carcinoma following definitive chemo‐radiotherapy. Issue 4 (7th May 2021) - Connor, Steve; Sit, Cherry; Anjari, Mustafa; Szyszko, Teresa; Dunn, Joel; Pai, Irumee; Cook, Gary; Goh, Vicky
Abstract: Background: Posttreatment diffusion–weighted magnetic resonance imaging (DW‐MRI) and 18F‐fluorodeoxygluocose ( 18 F‐FDG) positron emission tomography (PET) with computed tomography (PET/CT) have potential prognostic value following chemo‐radiotherapy (CRT) for head and neck squamous cell carcinoma (HNSCC). Correlations between these PET/CT (standardized uptake value or SUV) and DW‐MRI (apparent diffusion coefficient or ADC) parameters have only been previously explored in the pretreatment setting. Aim: To evaluate stage III and IV HNSCC at 12‐weeks post‐CRT for the correlation between SUVmax and ADC values and their interval changes from pretreatment imaging. Methods: Fifty‐six patients (45 male, 11 female, mean age 59.9 + − 7.38) with stage 3 and 4 HNSCC patients underwent 12‐week posttreatment DW‐MRI and 18 F‐FDG PET/CT studies in this prospective study. There were 41/56 patients in the cohort with human papilloma virus‐related oropharyngeal cancer (HPV OPC). DW‐MRI (ADCmax and ADCmin) and 18 F‐FDG PET/CT (SUVmax and SUVmax ratio to liver) parameters were measured at the site of primary tumors (n = 48) and the largest lymph nodes (n = 52). Kendall's tau evaluated the correlation between DW‐MRI and 18 F‐FDG PET/CT parameters. Mann‐Whitney test compared the post‐CRT PET/CT and DW‐MRI parameters between those participants with and without 2‐year disease‐free survival (DFS). Results: There was no correlation between DW‐MRI and 18 F‐FDG PET/CT parameters on 12‐week posttreatment imaging ( P = .455‐.794; tau = −0.075‐0.25) or their interval changes from pretreatment to 12‐week posttreatment imaging ( P = .1‐.946; tau = −0.194‐0.044). The primary tumor ADCmean ( P = .03) and the interval change in nodal ADCmin ( P = .05) predicted 2‐year DFS but none of the 18 F‐FDG PET/CT parameters were associated with 2‐year DFS. Conclusions: There is no correlation between the quantitative DWI‐MRI and 18 F‐FDG PET/CT parameters derived from 12‐week post‐CRT studies. These parameters may be independent biomarkers however in this HPV OPC dominant cohort, only selected ADC parameters demonstrated prognostic significance. Study was prospectively registered at http://www.controlled-trials.com/ISRCTN58327080